Analysis of the Influence of Organizational Culture on Employee Job Satisfaction in Multinational Companies - Dion Eko Prihandono; Efendy , Robby (CV. HEI PUBLISHING INDONESIA, 2024)
Organizational culture has long been recognized as one of the factors that greatly influences employee performance and job satisfaction in companies, especially on a global scale such as multinational companies (Garnida, 2011; Santoso, 2020). In the era of globalization, multinational companies are often faced with unique challenges related to cultural diversity, cross-border human resource management, and adaptation to different values (Nurfatmala et al., 2023; Sesariza, 2020). This study aims to analyze the influence of organizational culture on employee job satisfaction in multinational companies. Research Design This study uses a quantitative design with a correlational survey approach. In the organizational culture profile, the teamwork aspect scored the highest, with an average score of 4.5, indicating that teamwork and collaboration are very important in the organization. The level of employee performance shows that Job Quality received the highest average score (4.3), indicating that employees produce high-quality work. From the results of the analysis, it can be seen that the leadership aspect has the strongest influence with a regression coefficient of 0.40 and a significant value of p = 0.0000. Based on data analysis, the influence of organizational culture on employee job satisfaction in the context of this multinational company is very relevant to various theories of motivation, leadership, and management